The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1183/09031936.05.00082904
|View full text |Cite
|
Sign up to set email alerts
|

Cognition, sleep and respiration in at-risk children treated for obstructive sleep apnoea

Abstract: Sleep-disordered breathing in children has been associated with cognitive impairment. The purpose of this study was to examine the impact of tonsillectomy and adenoidectomy (T&A) on sleep, respiration and cognitive function in children of pre-school age with obstructive sleep apnoea (OSA) from a low-income community population.Altogether, 19 children attending state-funded pre-school programmes underwent overnight polysomnography and cognitive assessment before and following surgical treatment for OSA; 19 matc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
93
0
9

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(104 citation statements)
references
References 39 publications
2
93
0
9
Order By: Relevance
“…[22][23][24][25][26][27][28][29][30] The plausibility of the obstructive sleep apnea syndrome contributing to cognitive deficits is supported by research showing impaired learning in juvenile rats exposed to intermittent hypoxemia 3 and by imaging studies showing cerebral neuronal injury in children with the syndrome. 30 Previous studies have shown differences in the cognitive function of children with the obstructive sleep apnea syndrome, as compared with controls.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…[22][23][24][25][26][27][28][29][30] The plausibility of the obstructive sleep apnea syndrome contributing to cognitive deficits is supported by research showing impaired learning in juvenile rats exposed to intermittent hypoxemia 3 and by imaging studies showing cerebral neuronal injury in children with the syndrome. 30 Previous studies have shown differences in the cognitive function of children with the obstructive sleep apnea syndrome, as compared with controls.…”
Section: Discussionmentioning
confidence: 74%
“…19,27,31 However, baseline cognitive scores of children with the obstructive sleep apnea syndrome fell within the normal range, a finding similar to that in the current study. Cognitive and behavioral abnormalities have been shown to be reduced after adenotonsillectomy in some, [24][25][26][27]29 but not all, 30 nonrandomized studies, with inconsistency in the reported effect after treatment. 25,29,32 Previous studies have been limited by small samples, lack of randomization or appropriate controls, heterogeneous study groups, and sole reliance on parent questionnaires rather than including neuropsychological testing.…”
Section: Discussionmentioning
confidence: 99%
“…Those students who had lower grades were more likely to have snored during early childhood than children with better academic performance. Just like the behavioral problems, cognitive p er forman ce improved in children who underwent adenotonsillectomy to treat obstructive sleep apnea 26 .…”
Section: -Introduction: the Etiology And Sequela Of Osasmentioning
confidence: 99%
“…In one study, such children were 8 times more likely to develop cognitive problems compared to normal children. Academic performance often suffers in children with sleep-disordered breathing 26 . Gozal et al 14 studied over 1500 middle school children who were in the top 25% of their class and the bottom 25% of their class.…”
Section: -Introduction: the Etiology And Sequela Of Osasmentioning
confidence: 99%
“…In this issue of European Respiratory Journal, the study by MONTGOMERY-DOWNS et al [12] examines the impact of adenotonsillectomy for OSAS in pre-school-aged children from a lowincome community population. Previous studies have been restricted by small numbers of children from a wide age range who were referred because of a sleep disturbance.…”
mentioning
confidence: 99%